Socio-demographic characteristics of Uglich and Uglich uyezd monasteries inhabitants in the early 20th century - Leonov Dmitry Yevgeniyevich (Studia Humanitatis, 2023)
The article studied the inhabitants’ contingent of Uglich and Uglich Uyezd Orthodox monasteries in the early 20th century, based on the materials of the annual monastic reports from the collection of the State Archive of the Yaroslavl region. The characteristic of the education level of monastics and novices, their age, social origin is given. The use of sources over various years allowed us to trace the movement of the monasteries contingent inhabitants in dynamics. At the beginning of the 20th century, there were five monasteries in Uglich and its Uyezd: two nunneries and three friaries. The number of monks and novices in the two nunneries was twice as large as the total number of inhabitants of the friaries. Both nunneries and friaries were dominated by people from the peasant class. According to the level of education, the inhabitants were closer to the common people than to the parish clergy.